Increased Expression of Epidermal Growth Factor Receptor (EGF-R) in Patients with Different Forms of Lung Fibrosis. (6th June 2013) - Tzouvelekis, Argyris; Ntolios, Paschalis; Karameris, Andreas; Vilaras, George; Boglou, Panagiotis; Koulelidis, Andreas; Archontogeorgis, Kostas; Kaltsas, Konstantinos; Zacharis, George; Sarikloglou, Evangelia; Steiropoulos, Paschalis; Mikroulis, Dimitrios; et al.
Abstract : Introduction . Emerging evidence supports the role of epidermal growth factor-receptor (EGFR) in fibrogenesis. The aim of our study was to investigate the expression profiles of EGFR in three forms of IIPs, including idiopathic pulmonary fibrosis (IPF), cryptogenic organizing pneumonia (COP), and nonspecific interstitial pneumonia (NSIP). Patients and Methods . Twenty newly diagnosed patients with IPF, 15 with COP, and 15 with NSIP (cellular, n = 4 and fibrotic, n = 11 ) were investigated. Fifteen paraffin blocks obtained from the normal part of lungs removed for benign lesions were used as controls. Immunohistochemistry was carried out using specific monoclonal antibody. Results were verified by qRT-PCR. Results . A significant EGFR upregulation, both in protein and mRNA level, was observed in IPF, COP, and fibrotic NSIP samples compared to controls. EGFR was primarily localized in the hyperplastic alveolar epithelium surrounding areas of fibrosis in IPF, COP, and fibrotic NSIP samples, as assessed by double immunohistochemistry analysis with surfactant protein-A. EGFR mRNA levels were positively associated with indicators of lung fibrosis (type 1 collagen mRNA levels) and negatively correlated with functional prognostic parameters. Conclusions . We conclude that EGFR is upregulated in the hyperplastic alveolar epithelium in all three fibrotic forms of IIPs indicating a potential role during abnormal reepithelization.